1995
DOI: 10.1084/jem.181.4.1507
|View full text |Cite
|
Sign up to set email alerts
|

Somatic diversification and selection of immunoglobulin heavy and light chain variable region genes in IgG+ CD5+ chronic lymphocytic leukemia B cells.

Abstract: SummaryChronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of CD5-expressing B lymphocytes. Most studies have found that these leukemic CD5 + B cells, like their normal counterparts, use immunoglobulin (Ig) variable (V) region genes that exhibit minimal, if any, somatic diversity. These and other observations have suggested that CD5 § B cells may be incapable of generating Ig V gene diversity, and therefore may not be able to develop higher affinity binding sites that could be selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 52 publications
6
69
0
1
Order By: Relevance
“…Although we found that the V H 3 family was the most frequently involved in functional rearrangements, followed by V H 4 and V H 1, in agreement with Pasqualucci et al (2000), several reports have shown V H 3 followed by V H 1 and V H 4 (Fais et al, 1998;Pritsch et al, 1999;Sakai et al, 2000;Duke et al, 2003;Vilpo et al, 2003) or V H 4 > V H 3 > V H 1 profiles (Hashimoto et al, 1995). The occurrence of V H 1 as the third most frequent family coincided with the profile of normal cells (Rassenti et al, 1995;Matsuda et al, 1998), although, in most CLL studies, it was found only V H , D and J H immunoglobulin segments in Brazilian CLL patients 645 when the V H 1-69 segment was excluded from the analyses (Oscier et al, 1997;Duke et al, 2003).…”
supporting
confidence: 79%
“…Although we found that the V H 3 family was the most frequently involved in functional rearrangements, followed by V H 4 and V H 1, in agreement with Pasqualucci et al (2000), several reports have shown V H 3 followed by V H 1 and V H 4 (Fais et al, 1998;Pritsch et al, 1999;Sakai et al, 2000;Duke et al, 2003;Vilpo et al, 2003) or V H 4 > V H 3 > V H 1 profiles (Hashimoto et al, 1995). The occurrence of V H 1 as the third most frequent family coincided with the profile of normal cells (Rassenti et al, 1995;Matsuda et al, 1998), although, in most CLL studies, it was found only V H , D and J H immunoglobulin segments in Brazilian CLL patients 645 when the V H 1-69 segment was excluded from the analyses (Oscier et al, 1997;Duke et al, 2003).…”
supporting
confidence: 79%
“…[1][2][3][4][5] Such studies led to the discovery of quasi-identical or stereotyped BcR IGs in more than 30% of CLL patients who can be assigned to distinct subsets, each defined by a particular BcR immunogenetic motif. [6][7][8][9][10][11][12][13][14] Importantly, from both a biological and clinical perspective, evidence suggests that this classification of CLL based on BcR stereotypy is highly relevant and extends well beyond the SHM status of the BcR IG, thereby enabling the identification of homogeneous disease subgroups and, hence, overcoming the heterogeneity characteristic of CLL.…”
Section: Different Spectra Of Recurrent Gene Mutations In Subsets Of mentioning
confidence: 99%
“…19,20 A critical question in CLL biology is whether interaction with antigen is restricted to the progenitor cell (pre-transformation phase) or whether the putative antigen may continuously trigger the CLL clone and, perhaps, drive its evolution. [22][23][24][25][26][27] The experience from other types of B-cell malignancies suggests that useful hints for an ongoing interaction with antigen may be obtained through the study of intraclonal diversification (ID) within the IG genes expressed by the malignant clone. 28 With this in mind and through a recent comprehensive analysis of ID in rearranged IGHV genes from patients with CLL, we showed that although the majority of cases showed no or low levels of ID, an intense and, likely, functionally driven ID process was evident in selected cases, especially those belonging to subset 4.…”
Section: Introductionmentioning
confidence: 99%